FDTD investigation of adiabatic optical coupling between Silicon nitride and Germanium-based optical structures for energy-efficient photonic integration - Natdanai Khongpetch; Papichaya Chaisakul; Worawat Traiwattanapong; Surasak Chiangga; Pichet Limsuwan (My University, 2023)
Abstract This paper aims to investigate the potential of a direct integration between Si 3 N 4 waveguides and Germanium(Ge)-based structures, which are considered two of the most promising silicon(Si)-compatible materials for passive and active functions for Si-based energy-efficient photonics, respectively. This paper focuses on investigating the vertical coupling scheme between these materials employing a tapered structure of the Ge-based layer using 2D FDE and 3D FDTD simulations, to match the optical mode from a passive Si 3 N 4 waveguide to the Ge-based layer and vice versa. The expected optical coupling performance will be reported, and its dependence on the unavoidable fabrication variation in the coupling region will be also investigated. Additionally, the coupling performance of the vertical coupling approach compared to the previous investigation between a Si waveguide and a Ge layer will be addressed.
Keywords: Waveguide; Photonic and Optical Devices